Structure and function of human skeletal muscoles fibres - Bottinelli, R. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The large skeletal muscle heterogeneity and plasticity is based on both quantitative (alteration in the amount of a protein) and qualitative (alteration in the distribution of isoforms of a protein) mechanisms. The heterogeneity in force and power is though to be mainly based on muscle fiber hypertrophy and atrophy (quantitative mechanism), and on the differential distribution in muscles of fiber types containing specific myosin isoforms and having distinctive functional properties (qualitative mechanism). In adult human skeletal muscle three myosin heavy chain (MHC) isoforms are normally expressed: MHC-1, MHC-2A and MHC-2X. Three pure and two hybrid fiber types are identified on the basis of MHC isoform content: type 1, 2A and 2X (pure) and type 1-2A and 2AX (hybrid). Type 1 fibers have significantly lower maximum shortening velocity (Vo), maximum power (Wmax), and ATPase activity (ATPase) and Po/CSA than type 2X fibers. MHC-2A containing fibers (type 2A fibers) are intermediate. The large metabolic diversity of skeletal muscle fibers is also based on quantitative (oxygen supply from the capillary vessels, oxygen storage in myoglobin, mytochondria content) and qualitative (presence of specific isoforms of metabolic enzymes) mechanisms. A decrease, disuse (bed rest or space flight), or an increase (exercise training) of neuromuscular activity are likely the main determinants of skeletal muscle protein expression. Ageing has also a very clear impact on skeletal muscle structure and function. Muscle mass has been shown to decrease in disuse and ageing, increase following strength/sprint training and do not change following endurance training. In ageing some evidence suggests a preferential atrophy of fast (type 2A and 2X) fibers, consistently with the more evident age related denervation of fast than of slow motor units, whereas no such phenomenon has been so far demonstrated in disuse. Changes in fiber type distribution are rather variable in most conditions and from subject group to subjects group. Following strict immobilization or in paraplegic subjects the "default" fast muscle phenotype has been seen to emerge determining a shift towards fast fiber types, whereas following bed rest and spaceflight no consistent change has been observed. The partial denervation of muscle fibers that occurs in ageing is more evident for fast fibers and should determine a shift towards a slower phenotype. However, in ageing as in disuse, changes in myosin heavy chain isoform content has been shown to vary from subjects group to subjects group. It is now well established that in humans both endurance and resistance training determines a fiber transformation in the direction type 2X > 2A, whereas the opposite transformation 2A > 2X has not been documented in any exercise paradigm and the possibility of a shift 2A > 1 (following endurance training) is uncertain. This observations are difficult to reconcile with findings indicating that marathon runners have a high percentage of slow fibers and sprinters have high percentage of fast fibers, unless a significant role is attributed to genetic background. A clear increase in aerobic enzymes has been observed following endurance training in the absence of a clear increase in slow fibers relative content. This would imply an uncoupling between the synthesis of myofibrillar proteins and that of metabolic enzymes. No clear impact of strength training on metabolic enzymes activity has been shown so far. On the basis of the known mechanisms of muscle plasticity, it would be expected that a fiber type have the same specific force and shorten at the same velocity regardless the origin from an atrophic or hypertrophic or elderly muscle. However, a decrease in Po/CSA and in Vo has been shown in ageing and a decrease in Po/CSA and an increase in Vo has been shown following disuse when corresponding fiber types, containing therefore the same MHC isoform, are compared. As regards the effect of training, an increase in Vo of type 1 fibers have been observed following endurance training, whereas no change has been seen following sprint training. Although limited information are available on the matter, it appears that additional mechanisms of muscle plasticity, but the ones above reported, emerge in some conditions and modulate contractile properties of muscle fibers. A detailed description of contractile and energetic properties of single human muscle fibers and of possible mechanisms of muscle plasticity in addition to the well known qualitative and quantitative mechanisms will be reported and discussed at the symposium.